Proceedings of the 2014 ACM International Symposium on Wearable Computers 2014
DOI: 10.1145/2634317.2634338
|View full text |Cite
|
Sign up to set email alerts
|

Accommodating user diversity for in-store shopping behavior recognition

Abstract: This paper explores the possibility of using mobile sensing data to detect certain in-store shopping intentions or behaviours of shoppers. We propose a person-independent activity recognition technique called CROSDAC 1 , which captures the diversity in the manifestation of such intentions or behaviours in a heterogeneous set of users in a data-driven manner via a 2-stage clustering-cum-classification technique. Using smartphone based sensor data (accelerometer, compass and Wi-Fi) from a directed, but real-life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…To address this, CSI-based sensing can be combined with activity recognition through shopper's wearable/mobile devices [6,7]. Such hybrid approach can overcome some of the limitations of CSI-based analytics by improving classification with multiple shoppers and fine-grained activity recognition.…”
Section: Potential and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this, CSI-based sensing can be combined with activity recognition through shopper's wearable/mobile devices [6,7]. Such hybrid approach can overcome some of the limitations of CSI-based analytics by improving classification with multiple shoppers and fine-grained activity recognition.…”
Section: Potential and Limitationsmentioning
confidence: 99%
“…Simply relying on video surveillance to understand shopper's behavior is not scalable, given that deployment of video cameras and mining the video stream to extract information can have very high cost along with some serious privacy implications. Recent works [6,7] have proposed to use a user-driven approach where inertial sensors and camera available on shopper's wearable devices are used for physical analytics. However, this approach requires the shoppers to carry such devices and also e↵ectively communicate the acquired information to the business owner.…”
Section: Introductionmentioning
confidence: 99%
“…However a major drawback of personalized models is that they do not scale easily. In [10], we showed that with minimized personalized training, we could build a system which could recognize shopping behavior moderately well. Data from users who were similar to the individual was used to identify the behavior.…”
Section: Challengesmentioning
confidence: 99%
“…Shopping -The first ADL that we wanted to monitor was the individual's shopping behavior [10] -specifically, to distinguish between users with no buying intentions and shoppers (with buying intent) who were confused or focused. We performed a small scale user study with participating shoppers, where we collected sensor data (accelerometer, gyroscope and Wi-Fi) from their smartphones.…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation